Smart Learning for Sustainable Futures: Implementing an IoT-Based Light Detection Project Using Micro:bit Secondary Education - Dhistianti Mei Rahmawantary; Yuaniko Yuaniko; Pretty Failasufa Aziza; Retno Dwi Rahayu; Salwa Salsabila Firdaus (Santoso Academy Network, 2026)
This community service program aimed to enhance digital literacy, technological understanding, and sustainability awareness among secondary school students through an IoT-based light detection project using BBC Micro:bit. The program addressed students' limited exposure to practical Internet of Things applications and energy-efficient technologies in school learning environments. A Project-Based Learning (PjBL) approach was applied through interactive workshops involving IoT concepts, sensor technology, and block-based programming using the MakeCode platform. Participants designed and tested a light-detection system capable of automatically responding to environmental lighting conditions. Program evaluation was conducted using observations, practical assessments, questionnaires, and reflective discussions to measure participants' understanding, technological skills, and learning engagement. The findings indicated improvements in students' understanding of IoT concepts, programming logic, sensor applications, and awareness of energy efficiency practices. Participants also demonstrated increased confidence, collaboration, and problem-solving abilities during practical activities. In addition, teachers gained insights into integrating technology-based and sustainability-oriented learning into classroom instruction. The program highlights the potential of experiential IoT learning to support STEM education, strengthen digital competencies, and promote environmentally responsible behavior among secondary school students